Trends in the Internationalisation of R&D: The German Perspective - Marian Beise; Heike Belitz (Deutsches Institut für Wirtschaftsforschung (DIW), 1998)
In this paper we present latest facts about the R&D activities of German multinational companies abroad and R&D activities of foreign companies in Germany. These results confirm that Germany is still an attractive location for R&D activites of multinational companies in many technological fields. However, the internationalisation of R&D is closely linked with the internationalisation of sales and production. In the commonly accepted eclectic theoretical approach by Dunning direct investment is pushed by companies that have advantages over their competitors in the host countries, where also attractive locational advantages exist. Since R&D is a source of both ownership and locational advantages, it was suggested earlier that instead of owning a technological advantage, companies with technological weaknesses start R&D in countries, which possess a technological advantage, to get access to new technologies. In contrast we found that German firms prefer to do R&D abroad in technological fields in which they hold a technological lead, e.g. in chemicals, pharmaceuticals and motor vehicles, but that they tend to perform R&D in countries which are also strong in these fields. Our results suggest that in most cases it is not the technological superiority of the host country itself which is the decisive locational advantage to attract multinationals' R&D but the lead-market function of that country or region.
Keywords: F23; O32; 330; Multinational company; R&D; Internationalisation; Industrielle Forschung; Multinationales Unternehmen; Wettbewerb; Welt; Bundesrepublik Deutschland